Analisis Metode Penilaian Persediaan dan Penyajiannya Dalam Laporan Keuangan pada PT. United Traktor TBK Makassar - Eldi Eldi (Jurnal Ekonomika, 2013)
The aim of this research was to determine the method used in appraisal goods supply at PT. United Tractors Tbk Makassar and analyzed the way of presenting supply in financial statement company. method of analysis used was comparative analysis which compared, The result of this study showed that the company appraised its supply based on main cost in average method moves